Pendekatan Terhadap Penyampaian Ceramah Ustaz Kazim Elias Melalui Pengaplikasian Retorik Moden (Jurnal Bahasa, 2022)
Language plays a major role in a society especially in da’wah communication because every message in da'wah should be delivered using an accurate and precise language to ensure that the listener understands the meaning conveyed. Therefore, it is undeniable that some of the da'wah's message did not reach its listeners due to the preacher's failure in delivering and using language. As a result, the rhetorical approach is needed in order to improve the language used in processing or delivering the information so that it can be able to influence the listener. Although the rhetorical approach is often used in the field of education, politics and advertising, but this rhetorical theory also exists and is able to improve the quality of language in delivering the elements of da'wah. On that basis, this study focuses on the type and function of rhetoric used by speakers from neighboring countries, namely Ustaz Kazim Elias. Recordings of his talks were downloaded through the website and subsequently transcribed for research data. This study will utilize rhetorical theory as the main guide in parsing and explaining certain expressions according to the context in which they are spoken. Based on the analysis and discussion that has been done, this study found that there are all types of rhetoric used by Ustaz Kazim Elias (exposure: 31%, argument: 5%, explanation: 19%, narration: 37% and persuasion: 8%). These types can be identified through certain markers such as the use of pronouns, affirmative words, adjectives, figurative language (simile and metaphor) and verses of the Qur'an.Keywords: Da’wah communication, rhetoric, influence, creativity, contexFull text: PDF